Influência dos fatores climáticos no desempenho de módulos fotovoltaicos em regiões de clima tropical - Cantor, Guillermo Andres Rodriguez (2017)
Regions with tropical climate, like the Brazilian northeast, offers different real conditions compared with the STC conditions, for Photovoltaic (PV) systems. Because of that, this study collected different researches and expressions used to calculated the FV operating temperature (Tc), in order to determine which of those expressions better approach to the measured Tc under real operating conditions for a PV system connected to the grid, in a tropical region. During this study, were determined that apart of the ambient temperature, the irradiance and the wind speed, the relative humidity can also affects the PV performance and temperature, because the relative humidity interrupts the solar irradiance rays, and also increases the cell temperature. Out of ten equations found in the literature, the expressions that better approach to the measured cell temperature (Tc) were the proposed by Tamizhmani (±2,11%) and Loveday & Taki (±3,25%). Using the measured database, and considering the relative humidity, it was also proposed a new linear model for Tc, with a MAE (Mean Absolute Error) of ±1,45%, suitable for the m-Si PV models installed on the CEAR building, in a tropical climate.